2018
DOI: 10.31235/osf.io/2kdfy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the human dimensions of coexistence between carnivores and people: A case study in Namibia

Abstract: Many carnivore populations were in decline throughout much of the 20 th century, but due to recent conservation policies, their numbers are stabilising or even increasing in some areas of the world. This, compounded with human population growth, has caused increased livestock depredation by carnivores, which threatens farmer livelihoods, particularly those in developing countries such as Namibia. How to resolve this so-called "conflict" between carnivores and livestock farmers remains challenging, in part beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 260 publications
(451 reference statements)
0
4
0
Order By: Relevance
“…They agreed that training farm workers to improve their livestock husbandry and teaching people about carnivores could reduce conflict. Farm workers in Namibia tend to be from poor backgrounds and have limited education (Hunter, 2004), and therefore it is possible that educating them about effective husbandry will benefit the situation (Rust, 2015b). Previous research has shown that increased knowledge of carnivores and livestock husbandry practices can increase tolerance and reduce livestock depredation on Namibian farms (Marker et al, 2003), thus the Delphi/Q-methodology has successfully highlighted areas of agreement that reflect effective solutions to mitigating human–wildlife conflict.…”
Section: Discussionmentioning
confidence: 99%
“…They agreed that training farm workers to improve their livestock husbandry and teaching people about carnivores could reduce conflict. Farm workers in Namibia tend to be from poor backgrounds and have limited education (Hunter, 2004), and therefore it is possible that educating them about effective husbandry will benefit the situation (Rust, 2015b). Previous research has shown that increased knowledge of carnivores and livestock husbandry practices can increase tolerance and reduce livestock depredation on Namibian farms (Marker et al, 2003), thus the Delphi/Q-methodology has successfully highlighted areas of agreement that reflect effective solutions to mitigating human–wildlife conflict.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of homophily (the degree to which actors associate themselves with similar people; akin to "in-groups" discussed below) plays an important role for trust building over long distances. Homophily is influential if people attribute trustworthiness to others based on the other person's network position or organisational/institutional affiliations, or having the same culture or ethnicity (Rogers, 2003). Based on stereotypes, trust can even be assigned to roles and public figures that one trustee has never met in person (Henry & Dietz, 2011).…”
Section: Trustmentioning
confidence: 99%
“…Observations are recorded on a particular scenario and immediately analysed to determine if there are recurrent themes that should influence the direction of the research topic (Glaser & Strauss, 1967). For a more detailed description and justification of this approach, along with the methods, interview questions, sampling strategy and data analysis used in Rust et al (2016), see Rust (2015).…”
Section: Undertaking a Qualitative Studymentioning
confidence: 99%